On the global integration of REITs market returns: A multiresolution analysis - Kola Ijasan; George Tweneboah; Maurice Omane-Adjepong; Peterson Owusu Junior (Cogent Economics & Finance, 2019)
This paper explores dynamic correlation and interdependence of five global REIT markets using multivariate wavelet methods. United States, Hong Kong, Belgium, South Africa and Australia's daily REITs returns are used as proxies for North America, Asia, Europe, Africa and the Oceania continents, respectively. Highlights from our results indicate the following: First, almost a perfect market integration at long-run periods for the REIT markets is observed. However, such strong market correlations dissipate significantly to moderate and weaker linkages at the medium, and short-run periods, thereby showing possible diversification opportunities at the latter scales. The finding also signifies that global REITs linkages increases with investment horizons. Second, an interdependent global market is found, where well-developed REITs tend to lead/lag relatively smaller or less developed market (especially Africa's REIT) across scales. Third, there are prospects of gaining higher expected daily returns per unit of risk from Europe and Asia's REITs than all other markets. Though not totally integrated, there exist conspicuous evidence against a segmented global REIT market. Our findings are useful for improving portfolio selection and minimising trading risk.
Keywords: C22; F21; G1; G32; 330; Global REITs; multiresolution analysis; MODWT; scale; diversification